A NEW METHOD FOR PREDICTING FATIGUE LIFE UNDER TENSION-TORSIONAL LOADING - ZHANG YanJun; LEI MeiRong; SU Fang (Jixie qiangdu)
The established nonlinear fatigue damage model based on the theory of damage mechanics has been widely applied to multiaxial fatigue life prediction,however,this method does not consider the physical significance in the damage plane.This problem can be solved by combining with the critical plane method.Taking the thin-walled cylindrical specimen as the study object,a new damage parameter applicable to proportional and nonproportional multiaxial fatigue damage is proposed by means of von Mises rule based on the critical plane method with consideration of the influences of phase delay on the fatigue life are analyzed as well.The new defined damage parameter not only considers the maximum shear stain and normal strain on the critical plane,but also considers the effect of the additional cyclic hardening caused by the nonproportional loading on the fatigue life.The fatigue life predicted by the proposed damage model of three types of materials are proved to be in good agreement with experimental results.It is convenient for engineering application because the uniaxial fatigue data and material constants are considered only in this model.